Kaumātua, Leadership and the Treaty of Waitangi Claims Settlement Process; Some Data and Observations - Stephens, Māmari (Victoria University of Wellington Law Review, 2002)
This article presents the results of a survey dealing with the role of Kaumätua in Treaty of Waitangi Claims. The author raises a number of concerns – most importantly whether enough olderMäori feel confident or knowledgeable enough to contribute to the process. The survey also revealsthat tensions exist from the exclusion of younger Maori from the process.